NTU undergraduates perceptions of depression and gender stereotypes. - Prasad, Rina Hui-Min. (2009)
This paper aims to study on how Nanyang Technological University (NTU) undergraduate students perceive depression in relation to gender stereotypes. In my study, I focus on the kinds of gender attributes linked to students’ perception of depression. First, I examine how undergraduates perceive biological differences between genders as females’ hormonal changes contribute to their proneness to depression. Second, I examine the aspect of students’ perceptions of gender differences in coping strategies. Students usually think that males are better at externalizing or concealing their negative emotions through explicit means or externalization of emotions unlike females who engage in internalization of emotions, resulting in them being more depression-prone. Third, I examine how students perceive that the egalitarian gender ideology of modern day women which requires them to strike a balance between the dual spheres of the household and workplace thereby contributing to their depression.